2016
DOI: 10.1111/gwat.12417
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Elevated Levels of Arsenic in Public Wells of Bangladesh Due To Improper Installation

Abstract: One of the mainstays of mitigation to reduce the exposure of the rural population of Bangladesh to arsenic (As) from private, mostly <90 m deep wells over the past 15 years has been the installation of over 300,000 deeper community wells. A comprehensive testing campaign previously conducted across a 180 km2 of area of Bangladesh identified 9 out of total of 927 wells >90 m deep that contained >50 μg/L arsenic. We show here that for 5 of these 9 wells, conductivity profiles obtained after spiking the well bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The detection of modern tracers at some deep abstraction wells raises concerns about the vulnerability of these sites from shallow groundwater. The high salinity present at intermediate depths (Figure ) rules out vertical migration of shallow groundwater within the aquifer system and strongly suggests that these observations reflect short circuiting of shallow groundwater within pumping wells rather than vertical mixing within the local or regional aquifer system (I. Choudhury et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The detection of modern tracers at some deep abstraction wells raises concerns about the vulnerability of these sites from shallow groundwater. The high salinity present at intermediate depths (Figure ) rules out vertical migration of shallow groundwater within the aquifer system and strongly suggests that these observations reflect short circuiting of shallow groundwater within pumping wells rather than vertical mixing within the local or regional aquifer system (I. Choudhury et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Regional‐scale modeling (Burgess et al, ; Hoque et al, ; Michael & Voss, , ) and field studies (McArthur et al, ; Mihajlov et al, ; Mukherjee et al, ; Ravenscroft et al, ) have explored the vulnerability of the deep groundwater in the coastal Bengal Aquifer System (BAS) to contamination yet key knowledge gaps remain. These include the relative importance of site‐specific, borehole‐ scale problems due to casing breaks at abstraction well sites (I. Choudhury et al, ) and aquifer‐scale vulnerabilities (Hoque et al, ) to contamination from shallow groundwater and the long‐term impacts of intensive pumping at depth (Khan et al, ; Knappett et al, ; Michael & Khan, ; Zahid et al, ). The presence of modern tracers (e.g., tritium and chlorofluorocarbons (CFCs)) in deeper groundwater systems (typically >150 m) has been attributed to deep pumping in the BAS and in many other aquifer systems globally (Jasechko et al, ; Lapworth et al, ; McMahon et al, ; Samborska et al, ) yet considerable uncertainty remains about the scale and nature of this pumping‐induced contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the transitional aquifer is referred to as “shallow” low‐As aquifer (<90 m bgl), whereas the deeper aquifers are split into “intermediate” (90–150 m bgl) and “deep” (>150 m bgl) categories. These definitions account for the drilling method used for well installations, as well as the government's Department of Public Health Engineering standard definition of wells deeper than 150 m as deep [ van Geen et al ., ; Choudhury et al ., ]. The shallow aquifer designates the low‐As aquifer that extends beneath the depth of peak As concentrations [ van Geen et al ., ] to the depth of ∼90 m bgl, within the reach of the traditional hand‐flapper installation method [ Ali , ; Horneman et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Other maps were prepared using the QGIS software. However, some isolated pockets of As contamination exceeding 50 μg/L may be due to incorrect reporting of well depth or construction defects (Aggarwal, Basu, & Poreda, ; Choudhury et al, ; Ravenscroft et al, ; Stahl et al, ), and where such evidence was demonstrated, the record was omitted (Data S3), but where no contradictory evidence was obtained, anomalous records were retained. The reasons for incorrect depths are often non‐scientific, but the practical implication is that individual outliers should be treated with caution, and our approach was to look for verification by identifying patterns and consistency between independent data sources.…”
Section: Data Sources and Processingmentioning
confidence: 99%